TEKNIK MODELLING TERHADAP KETERAMPILAN VOKASIONALSISWA TUNAGRAHITA RINGAN - KUSMIARTI, MAMIK (Jurnal Pendidikan Khusus, 2016)
ABSTRACTThe purpose of this research was to observe whether there was influence of modeling technique application towardvocational skill to mild mentally retardation students of class XI in SMALB-C AKW Kumara II Surabaya or not.The low intelligence level of mild mentally retardation students resulted the lack of thinking power and lack ofcreativity in arranging a product, in addition they were also demanded to have vocational skill in order that they couldbe autonomous. Therefore, to solve the problem it required learning which trained vocational skill and surely by usingthe technique which was suitable with the mild mentally retardation students’ characteristics. One of the techniqueswhich could be used was modeling technique. The method used in this research was quantitative approach with preexperimental design arrangement and one group pretest-posttest design. The sample in this research was 6 mildmentally retardation students of class XI in SMALB-C AKW II Surabaya. The data obtained from pretest and posttestwas analyzed by using the data analysis technique of statistic non parametric with quantitative data and using thesample less than 30 i.e. 6 students. The formula used to process the data was sign test. This research result indicated thatthe average pretest value was 56,08 while the average value obtained by the students in posttest was 94,11. The result ofdata analysis indicated Z counted was 2,05 and Z table with critic value 5% was 1,96. Through the analysis result itcould be concluded that Ho was refused and Ha was accepted, it meant that there was influence of modeling techniquetoward vocational skill to mild mentally retardation students in SMALB-C AKW Kumara II Surabaya.Keywords: Modeling technique, vocational skill